2020
DOI: 10.3390/jcm9113448
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inflammation and Calcification in Pseudoxanthoma Elasticum Arteries and Skin with 18F-FluroDeoxyGlucose and 18F-Sodium Fluoride Positron Emission Tomography/Computed Tomography Imaging: The GOCAPXE Trial

Abstract: Background: Pseudoxanthoma elasticum (PXE) is an inherited metabolic disease characterized by elastic fiber fragmentation and ectopic calcification. There is growing evidence that vascular calcification is associated with inflammatory status and is enhanced by inflammatory cytokines. Since PXE has never been considered as an inflammatory condition, no incidence of chronic inflammation leading to calcification in PXE has been reported and should be investigated. In atherosclerosis and aortic stenosis, positron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
0
25
0
1
Order By: Relevance
“…Our group has reported that in PXE patients this radiopharmaceutical is also deposited in the flexural areas of the skin (especially the neck and axillae), and that this deposit relates well to the severity of the lesions observed in physical examinations [8]. Identical data have been published more recently [9].…”
Section: Introductionmentioning
confidence: 75%
“…Our group has reported that in PXE patients this radiopharmaceutical is also deposited in the flexural areas of the skin (especially the neck and axillae), and that this deposit relates well to the severity of the lesions observed in physical examinations [8]. Identical data have been published more recently [9].…”
Section: Introductionmentioning
confidence: 75%
“…In PXE, atherogenesis is not yet fully understood. Although positron-emission tomography scans did not assess vascular inflammation in PXE patients [ 100 ], the presence of capillary alterations may indicate a role for the hypoxia-induced formation of reactive oxygen species as a second messenger in the pathophysiology of PXE [ 13 ]. A dysregulation of blood lipids also is part of the PXE phenotype [ 12 , 101 , 102 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…7,8 Importantly, in a crosssectional study, focal arterial [ 18 F]FDG uptake did not correlate with [ 18 F]NaF uptake. 9 Furthermore, arterial [ 18 F]FDG PET uptake was not associated with calcification progression on computed tomography (CT) and specific sites of increased [ 18 F]FDG uptake and calcification rarely overlapped. 10 However, since inflammation is the precursor of calcification development and previous studies observed that both processes are not present simultaneously, 9,11 we hypothesize that [ 18 F]FDG-assessed arterial inflammation may be associated with [ 18 F]NaF-assessed arterial microcalcification over time.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, arterial [ 18 F]FDG PET uptake was not associated with calcification progression on computed tomography (CT) and specific sites of increased [ 18 F]FDG uptake and calcification rarely overlapped. 10 However, since inflammation is the precursor of calcification development and previous studies observed that both processes are not present simultaneously, 9,11 we hypothesize that [ 18 F]FDG-assessed arterial inflammation may be associated with [ 18 F]NaF-assessed arterial microcalcification over time. The primary aim of this proofof-concept study is the assessment of the prospective association of baseline systemic arterial [ 18 F]FDG activity with systemic [ 18 F]NaF PET during five years of follow-up in asymptomatic patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%